Efek Hand Hygiene terhadap Dermatitis Tangan - Ricky Setiadi Yusuf (Faculty of Medicine Universitas Mataram, 2021)
In this pandemic COVID-19 era, it’s important to everyone that maintain cleanliness especially hand sanitation. Hand hygiene behavior is one of many ways that effective to prevent COVID-19. Generally, hand hygiene can be done by two methods, there are hand washing with water and using hand sanitizer. Exaggerating in hand hygiene make a new other health problem, that is hand dermatitis. Nowadays, health care workers are known to have a high risk of developing hand dermatitis due to their work. Based on World Health Organization (WHO), hand washing with water and soap can be done in 40 until 60 seconds, besides, hand washing with hand sanitizer can be done in 20 until 30 seconds. Therefore, prevention of hand dermatitis is important too. Applying moisturizer effectively can reduce the risk of hand dermatitis.